STRENGTHENING DIGITAL CITIZHENSHIP EDUCATION IN SOCIAL MEDIA TO GROW GOOD DIGITAL CITIZEN IN STUDENTS OF FKIP SYIAH KUALA UNIVERSITY - Ruslan Ruslan; Muhammad Haikal; Sulaiman Sulaiman (Sensei International Journal of Education and Linguistic, 2022)
The purpose of this study is to describe the Strengthening of Digital Citizhenship Education in Social Media to Grow Good Digital Citizens in FKIP students at Syiah Kuala University. The data collection method in this study used in-depth interviews, in-depth interviews were tried to get information that fits the research focus. This research uses a qualitative approach to the type of descriptive research. Descriptive research is research that is made with the main objective of givingan objective reflection of an atmosphere. The location of this research is at the FKIP of Syiah Kuala University, namely on Jl. date Hasan Krueng Kalee, Kopelma Darussalam, Kec. Syiah Kuala, Banda Aceh City. The results of this study are that the convenience of social media is very easy to access from the results of interviews from users who continue to use social media by respecting and appreciating differences (Respect) while maintaining emotional resilience,responsibility, responsibility, then other data are also found students think that in social media they need to analyze and seek the truth, logical thinking when doing activities on social media/cyberspace . then what is so important about this social media is good ethics, limiting time and being wise.